SPILLOVER EDUCATED OF INDONESIAN MIGRANT WORKERS (IMW) ON CENTRAL JAVA'S ECONOMIC GROWTH - Caroline Caroline; Pujiono Pujiono (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
Indonesian Migrant Workers (TKI) or now known as Indonesian Migrant Workers (IMW) contribute to the economic growth of Central Java Province through foreign exchange earnings, and increasing work productivity. The purpose of this study is to analyze the spatial interaction patterns of IMW locally and globally. This research method uses a euclidean distance weight matrix approach to calculate the Local Moran Index and the Global Moran Index. The novelty of this research is to consider Indonesian workers or IMW with higher education. The conclusion of this study is that the results of the Local Moran Index empirical research identify that there are similar or dissimilar patterns of spatial interaction (within in group) in Cilacap Regency, Brebes Regency, Kendal Regency. However, in 2021 Indonesian Migrant Workers (IMW) from Central Java identified a pattern of spatial interaction (within in group), both similar and dissimilar, in the positions of Cilacap Regency and Kendal Regency. Changes in the Local Moran's Index of Indonesian Migrant Workers (IMW) in 2010 and 2021 were allegedly due to the placement of the number of Indonesian Migrant Workers (IMW) to the destination country which was limited in 2021. Initially, Indonesian Migrant Workers (IMW) in 2010 were Indonesian Migrant Workers (IMW) its placements are in 27 countries, decreasing to 17 countries in 2021. The results of empirical research on the negative Global Moran's I coefficient on Indonesian workers (IMW) with higher education from 2010 to 2021 identify that the spatial interaction pattern of Indonesian workers (IMW) with higher education in Central Java Province is divergent or spreads from districts/cities to district/city.